2022
DOI: 10.1093/rheumatology/keac646
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β3 in differentiation and function of Tph-like cells and its relevance to disease activity in patients with systemic lupus erythematosus

Abstract: Objectives T peripheral helper (Tph) cells have major roles in pathological processes in systemic lupus erythematosus (SLE). We sought to clarify the mechanisms of Tph cell differentiation and their relevance to clinical features in patients with SLE. Method Phenotypes and functions of Tph cell–related markers in human CD4+ T cells purified from volunteers or patients were analyzed using flow cytometry and quantitative PCR. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Similarly, Bocharnikov et al and Shan et al reported that the frequency of PBMC-derived Tph cells was correlated with several SLE disease activity indices. 2,3 The sPD-1, sPD-L1, and sPD-L2 serum levels in 16-weekold BXSB-Yaa mice were significantly higher than those in 8week-old BXSB-Yaa and C57BL/6 mice and were correlated with clinical lupus activity in the present study. This is consistent with our previous report, in which the sPD-1 and sPD-L2 serum levels were increased in patients with SLE and associated with its disease activity.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Similarly, Bocharnikov et al and Shan et al reported that the frequency of PBMC-derived Tph cells was correlated with several SLE disease activity indices. 2,3 The sPD-1, sPD-L1, and sPD-L2 serum levels in 16-weekold BXSB-Yaa mice were significantly higher than those in 8week-old BXSB-Yaa and C57BL/6 mice and were correlated with clinical lupus activity in the present study. This is consistent with our previous report, in which the sPD-1 and sPD-L2 serum levels were increased in patients with SLE and associated with its disease activity.…”
Section: Discussionsupporting
confidence: 56%
“…2 In addition, T cell-B cell interactions within the peripheral inflamed sites can involve T peripheral helper (Tph) cells with distinct phenotypes from the germinal center Tfh cells. 3 Actually, Bocharnikov et al identified a highly expanded population of programmed cell death protein 1 (PD-1) high CXCR5 -CD4 + T cells in the peripheral blood mononuclear cells (PBMCs) of patients with LN, which were Tph cells that stimulated B cell responses via Division of Rheumatology, Department of Internal Medicine, Tokyo Women's Medical University School of Medicine, Tokyo, Japan interleukin-21 (IL-21). 2 In addition, the frequencies of Tph cells, but not Tfh cells, correlated with clinical disease activity, and the frequency of PD-1 high CD4 + T cells among the CD45 + leukocytes that were derived from LN kidney biopsy samples was increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, B cells from SLE patients cultured with TGF-β3 showed reduced B-cell survival, proliferation, and differentiation into plasmablasts and IgG, IgA, and IgM production and decreased the expression of IFN regulatory factor 4 (IRF4), B lymphocyte-induced maturation protein-1 (Blimp-1), X-box-binding protein 1 (XBP1), Smad1/5, and Syk ( 111 ). T peripheral helper (Tph)-like cells in SLE patients such as PD-1 hi MAF + cells, IL-21 + IL-10 + cells, and PD-1 hi CX3CR1 + cells stimulated with TGF-β3 showed increased proliferation of the cells and elevated expression of PDCD-1, SOX4, and CXCL13 ( 112 ). CXCR5 - PD-1 hi Tph cells cocultured with class-switch memory B cells in the presence of TGF-β3 revealed much class-switch memory B cells differentiated into plasmocytes and high expression of IgG and IgM, suggesting that TGF-β3 regulates differentiation and function of Tph-like cells in lupus ( 112 ).…”
Section: Th1-related Inflammatory Cytokinesmentioning
confidence: 99%
“…T peripheral helper (Tph)-like cells in SLE patients such as PD-1 hi MAF + cells, IL-21 + IL-10 + cells, and PD-1 hi CX3CR1 + cells stimulated with TGF-β3 showed increased proliferation of the cells and elevated expression of PDCD-1, SOX4, and CXCL13 ( 112 ). CXCR5 - PD-1 hi Tph cells cocultured with class-switch memory B cells in the presence of TGF-β3 revealed much class-switch memory B cells differentiated into plasmocytes and high expression of IgG and IgM, suggesting that TGF-β3 regulates differentiation and function of Tph-like cells in lupus ( 112 ). Injection of the poly(lactic-co-glycolic acid) nanoparticle encapsulating TGF-β into lupus mice induced expansion of CD4 + Foxp3 + Treg cells and CD8 + Foxp3 + Treg cells and suppression of anti-dsDNA antibody and reduced renal disease ( 113 ).…”
Section: Th1-related Inflammatory Cytokinesmentioning
confidence: 99%